A Randomized Controlled Trial Comparing Packing with Nonpacking of Perianal Abscess Cav - Islam, Md Tanvirul; Rahman, Md Mahbubur; Begum, Nasrin (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Anorectal abscess is a potentially debilitating condition and one of the common anorectal conditions encountered in practice. Anorectal abscesses are defined by the anatomic space in which they develop and are more common in the perianal and ischiorectal spaces. Traditional management of perianal abscess involves early incision, drainage, curettage and packing of the residual cavity. Cavity packing and dressings are problematic in that they cause significant discomfort and require multiple visits to change the packing until healing. An alternative to the traditional approach is to perform adequate incision and drainage and then to allow healing without the use of cavity dressings. Objective: To compare the effects of packing with nonpacking of the perianal abscess cavity on patient discomfort and wound healing and subsidiary evaluation of the clinical outcomes. Materials and Methods: This single centre randomized controlled trial was carried out on 50 patients who were operated upon for perianal abscess in Combined Military Hospital, Dhaka during the period of July 2014 to June 2016. Patients were randomly assigned to receive either packing or nonpacking treatment through allocation by sealed envelope. The packing (control) group was instructed to report to a single nursing staff for subsequent dressing with packing of the residual cavity. The nonpacking group was discharged with a superficial protective dressing; they did not undergo wound dressing but managed their own wounds until follow-up. Outcome measures were time of healing, abscess recurrence, fistula formation and post operative pain. Results: A total of 54 patients were enrolled (4 lost in follow-up): 24 in the packing and 26 in the nonpacking arm. The two groups were comparable in terms of age and gender distribution, type, size of the abscess, duration of symptoms and length of follow-up. Healing in the non-packing group was faster compared to that of the packing group: mean 24.08 days versus 34.13 days (P=0.000). The rate of abscess recurrence was similar (P=0.664). Post operative fistula rates were similar (P=0.623). Pain scores appeared less in the nonpacking arm and statistically significant (7.25 vs. 4.24, P=0.000). Conclusion: Small size of the study population was the limitation of this study. In order to obtain a higher level of evidence, an adequately powered multicentre based prospective randomized controlled trial is required to definitely address the question of packing of the cavity and its beneficial outcome following incision and drainage in the management of perianal abscess. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 111-116